EUROCENTRISMO E CURRÍCULO: ANÁLISE DAS CONCEPÇÕES CURRICULARES CRÍTICAS E NÃO CRÍTICAS A PARTIR DE UMA PERSPECTIVA DECOLONIAL E DA ECOLOGIA DE SABERES - Ribeiro, Débora (2018)
Latin American Decolonial Thought emerges from a group of theoretical epistemically located in the south of the world, whose reflections depart from the colonial wound, of those who had their voices and experiences suppressed by colonization and modernization. Therefore, the purpose of this research is to analyze the discussions about the curriculum and some alternative proposals of education headed by social movements through the decolonial thought, in order to contribute to a non-Eurocentric, decolonial e decolonizing curricular construction. For this purpose, I did a theoretical research looking for elements in decolonial thought and ecology of knowledges, in critical and noncritical theories of the curriculum, and in some alternative proposals of education headed by Latin American social movements, in order to contribute to the reflection on eurocentrism in the curriculum. From this analysis, it is perceived that the curriculum within the traditional trends, technical and renewed, represent several aspects of the coloniality of power, being and knowing, excluding the knowledge and identities of subalternized peoples and social groups. And that even when critical trends sought to rethink the curriculum within Western thought, this happened within the orientations of the Eurocentric thinking, although they constitute important contributions. However, the education alternatives of Latin American social movements, such as zapatismo, the indigenous and quilombola movements, point out and already construct a decolonial and non-Eurocentric education. The different types of knowledge are considered in fairness of dialogue, are redeemed and valued. Knowledge is built collectively, aimed at the interests of each community, to an epistemological pragmatics. The objectivity, neutrality, and universality of Western scientific knowledge are denied, and in its place is constructed a plural knowledge that is part of a paradigm of distinct thought, which sustains an forms part of other societies built daily by the resistances de abajo. These practices and thoughts indicate for the construction of another world in which there is no global hierarchy of the population in terms of race, color, work, sex, etc., where all knowledge is considered valid and all ways of being are recognized. Latin American social movements teach us that we need to learn, unlearn and relearn from the Western knowledge and hitherto subalternized knowledge.